Sampling method for surveying complex and multi-institutional partnerships: Lessons from the Global Polio Eradication Initiative - Peters, Michael A.; Deressa, Wakgari; Sarker, Malabika; Sharma, Neeraj; Owoaje, Eme; Ahmad, Riris Andono; Saljuqi, Tawab; Mafuta, Eric; Alonge, Olakunle (BMC, 2022)
This article was published in BMC Public Health by BMC [ © The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License,] and the definite version is available at: https://doi.org/10.1186/s12889-020-08592-x The Journal's website is at: https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-020-08592-x